2004
DOI: 10.1038/sj.thj.6200343
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of two portable systems for oral anticoagulant monitoring

Abstract: Portable prothrombin time (PT) monitors offer the potential for both simplifying and improving oral anticoagulation management. It is necessary to evaluate their concordance and correlation with other PT systems. Our objective was to evaluate the concordance and clinical correlation of two portable PT determination systems, ProTime (ITC) and CoaguChek S (Roche Diagnostics). In all, 20 healthy individuals and 60 anticoagulated patients stabilized over 3 months in a therapeutic International Normalized Ratio (IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The correlation between the INR values obtained with the Coaguchek S™ system and the laboratory tests was almost perfect 15 with a r s coefficient equal to 0.9, similar to the findings of other studies involving the Coaguchek S™ system and other prothrombin time control devices 6,16,17 . However, according to Bland and Altman 7 , correlation coefficients are not the best method to evaluate measurements between two methods, since this merely reveals the variation between the two results and not the absolute difference.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The correlation between the INR values obtained with the Coaguchek S™ system and the laboratory tests was almost perfect 15 with a r s coefficient equal to 0.9, similar to the findings of other studies involving the Coaguchek S™ system and other prothrombin time control devices 6,16,17 . However, according to Bland and Altman 7 , correlation coefficients are not the best method to evaluate measurements between two methods, since this merely reveals the variation between the two results and not the absolute difference.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies also report this consideration 6,17 . The quality of the Coaguchek S™ system is impaired for INR units above 4 when compared to laboratory measurements using sensitive thromboplastin.…”
Section: Discussionmentioning
confidence: 77%
“…The visual inspection of the diagram discloses an increase in the disagreement towards the higher INR averages, especially above 4.5. This is a foreseeable finding very well described in the previous bibliography studying the accuracy of portable devices (33,34) and even between standard methods with different thromboplastins (35) and it is probably related to the WHO guidelines to exclude samples with INR outside the 1.5-4.5 range for ISI assignment (24) which makes the ISI/INR system accurate only in that range explored by the calibration procedure.…”
Section: Discussionmentioning
confidence: 61%
“…Related studies have demonstrated that when the INR values exceeded the therapeutic range, the bias increased, especially when the INR values were above 4.5. [14,15] The higher SD when the INR was above 4.5 related to both the World Health Organization (WHO) guidelines, which exclude samples with an INR outside the range of 1.5-4.5 for the ISI assignment. [16] Also, ISO 17593:2007 excludes samples with an INR beyond 6.0.…”
Section: Accuracy Of the Coaguchek Xs Plus System Based On The Three mentioning
confidence: 99%